THE EFFECT OF FISCAL POLICY MEASURES ON SMALL-SCALE BUSINESSES DURING THE PANDEMIC: A CASE STUDY OF MUKONO MUNICIPALITY - OKELLO JOSHUA ATWOKO (UGANDA CHRISTIAN UNIVERSITY, 2024)
This study evaluates the impact of fiscal policy measures on small-scale businesses in Mukono Municipality during the COVID-19 pandemic, focusing on investment decisions, digital transformation, and innovation and product development. Using secondary data from government reports, economic surveys, and institutional publications, the study employed a descriptive research design to analyze the relationships between tax incentives, subsidies and grants, and loan guarantees with small-scale business outcomes. The findings revealed that tax incentives had a minimal positive impact on both investment decisions and innovation, suggesting that while they provided financial relief, their overall influence was limited. Subsidies and grants were more effective, showing a significant positive effect on digital transformation and innovation, enabling businesses to adopt new technologies and develop new products. However, loan guarantees harmed both investment decisions and innovation, reflecting business owners' reluctance to take on debt during the pandemic due to economic uncertainty. More targeted and flexible fiscal interventions, coupled with broader economic support, are recommended to enhance the resilience and growth of small-scale enterprises in future economic crises.
This is a study that seeks to determine the effectiveness of fiscal policy measures implemented by the Ugandan government during the pandemic in 2020. It assesses how the fiscal policy measures affected small-scale businesses in mukono municipality. It determines the effectiveness of the mentioned interventions by assessing the performance of small scale businesses.